European - ASEAN Regional Knowledge Sharing: Improving Competitiveness in Travel and Tourisme - Judith Marilyn Tomasowa (Proceeding Of The International Seminar and Conference on Global Issues, 2016)
Some European countries are famous for its competitiveness in travel and tourism as it was ranked by World Economic Forum in 2015-2016, based on 14 pillars related to sustainable society principles of human, environmental and economic wellbeings. ASEAN country members are diversed in ranks, due to its uniques strengths and weaknesses of each member countries.  ASEAN has benchmarked the European Union integration process, including the spirits of One Identity, One Vision, One Community, which applied in policies and regulations, such as the new ASEAN Tourism Strategic Plan 2016-2025. It stressed out competitiveness and sustainability, that may require for ASEAN to benchmark other regions that have implemented one single destination policy. ASEAN member countries should think as One Vision, One Identity and One Community, in discussion to find the best solution for all member countries, since the members should sacrifice its domestic and bilateral advantages, in order to gain ASEAN Regional advantages. This paper has identified 4 regional development priority levels based on 14 pillars of Competitiveness Index, 2015-2016  The WEF Report, 2016-2020 ASEAN Tourism Strategic Plan,  2015-2016 Travel & Tourism Competitiveness Index, and 2015 Global Benchmark Report,  includes other indicators, development rates and socio-economics statistics. This article’s is the presentation of the competitiveness and responsiveness concepts and its relation to solve a trilemma of sustainable society, that related to green supply chain management and international strategy in ASEAN. This article aimed to give recommendation to solve a ASEAN’s Trilemma in travel and tourism. Keywords: sustainability, competitiveness, tourism, benckmark, strategic plan.